Herpes zoster incidence in Germany: an indirect validation study for self-reported disease data from pretest studies of the population-based German National Cohort - Caputo, Mahrrouz; Becher, Heiko; Brenner, Hermann; Caputo, Mahrrouz; Horn, Johannes; Karch, André; Akmatov, Manas K.; Braun, Bettina; Castell, Stefanie; Fischer, Beate; Giani, Guido; Günther, Kathrin; et al. (BMC infectious diseases, 2019)
German National Cohort; Herpes zoster; Incidence; Postherpetic neuralgia; Self-reports; Validity